(untitled) (Research, Society and Development, 2020)
To evaluate the association between the obesogenic environment and the occurrence of overweight / obesity among adolescents. Case-control study conducted between July and October 2018, with adolescents (10 to 16 years) enrolled in public schools. “Cases” were defined as those who were overweight or obese, as “controls” the eutrophic, paired by sex, age and class. Demographic characteristics and those related to the obesogenic environment (using a form), in addition to the nutritional status of caregivers and adolescents (through anthropometry) were evaluated. Pearson’s chi-square test was applied, with Fisher adjustments, when necessary. SPSS 22.0 and a 95% confidence interval were used. Study approved by the Research Ethics Committee (CAAE 84019518.3.0000.5187). The nutritional status of caregivers was associated with that of adolescents (p <0.01). Regarding the characteristics of the surroundings of the home, it was observed that, with the exception of the presence of heavy traffic, most reported adequate conditions for the practice of exercises, however, there was no statistically significant association with the nutritional status of the adolescents, as well as with sedentary behaviors and eating habits considered inappropriate. There was a high percentage of adolescents who do not practice physical activity outside school (66%), who spend at least two hours a day in front of screens (86%) and who spend less than two hours in activities that make them run (80% ). All reported eating out at home five times a week. For the studied population, characteristics of the obesogenic environment were not associated with nutritional status.